Tuberculosis vaccines in clinical trials. - Rowland, R; Mcshane, H (2011)
Effective prophylactic and/or therapeutic vaccination is a key strategy for controlling the global TB epidemic. The partial effectiveness of the existing TB vaccine, bacille Calmette-Guérin (BCG), suggests effective vaccination is possible and highlights the need for an improved vaccination strategy. Clinical trials are evaluating both modifications to the existing BCG immunization methods and also novel TB vaccines, designed to replace or boost BCG. Candidate vaccines in clinical development include live mycobacterial vaccines designed to replace BCG, subunit vaccines designed to boost BCG and therapeutic vaccines designed as an adjunct to chemotherapy. There is a great need for validated animal models, identification of immunological biomarkers of protection and field sites with the capacity for large-scale efficacy testing in order to develop and license a novel TB vaccine or regimen.